We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
35
1
avatar

Let F1 and F2  be the foci of the ellipse kx^2+y^2=1 where k is greatr than 1 is a constant. Suppose that there is a circle which passes through F1  and F2  and which lies tangent to the ellipse at two points on the x-axis. Compute k.

 Mar 20, 2019
 #1
avatar+21978 
+2

Let F1 and F2  be the foci of the ellipse kx^2+y^2=1 where k is greatr than 1 is a constant.
Suppose that there is a circle which passes through F1  and F2  and
which lies tangent to the ellipse at two points on the x-axis.
Compute k.

 

We rearrange \(kx^2+y^2=1\):

\(\begin{array}{|rcll|} \hline \mathbf{kx^2+y^2} & \mathbf{=} & \mathbf{1} \\ \\ \dfrac{x^2}{\dfrac{1}{k}}+\dfrac{y^2}{1} &=& 1 \\\\ \dfrac{x^2}{ \left(\color{red}{\dfrac{1}{\sqrt{k}}} \right)^2 }+\dfrac{y^2}{{\color{red}1}^2} &=& 1 \quad | \quad \boxed{\dfrac{x^2}{a^2}+\dfrac{y^2}{b^2}=1 } \\\\ \mathbf{a} &\mathbf{=} & \mathbf{\dfrac{1}{\sqrt{k}}} \\ \mathbf{b} &\mathbf{=} & \mathbf{1} \\ \hline \end{array} \)

 

The formula with the focus of this ellipse is \(c^2= b^2-a^2\)
where \(c\) is the distance from the focus to origin.

 

\(\begin{array}{|rcll|} \hline c^2 &=& b^2-a^2 \quad & | \quad b=1,\ a=\dfrac{1}{\sqrt{k}} \\\\ &=& 1-\dfrac{1}{k} \\\\ \mathbf{c} &\mathbf{=}& \mathbf{\sqrt{1-\dfrac{1}{k}} } \\ \hline \end{array} \)

 

Circle: \(r = c=a\)

\(\begin{array}{|rcll|} \hline \sqrt{1-\dfrac{1}{k}} &=& \dfrac{1}{\sqrt{k}} \\\\ 1-\dfrac{1}{k} &=& \dfrac{1}{k} \\\\ 1 &=& \dfrac{2}{k} \\\\ \mathbf{k} &\mathbf{=}& \mathbf{2} \\ \hline \end{array}\)

 

laugh

 Mar 21, 2019

14 Online Users

avatar
avatar
avatar